Cover Image, Volume 172C, Number 3, September 2016. Issue 3 (September 2016) - Unknown
Abstract : The cover photographs were all taken by Rick Guidotti, famous photographer and founder of Positive Exposure, at the 2016 SOFT Conference in Tacoma, WA. The children have full trisomy 13 or 18 with the exception of one girl with trisomy 13 mosaicism.